Inhibitory actions of muscarinic cholinergic receptor agonists on serotonin N-acetyltransferase in bovine pineal explants in culture - P. Phansuwan Pujito (2018)
We have previously identified muscarinic cholinergic receptors in the bovine pineal gland with a KDvalue of 0.423±0.01 nM and a Bmaxvalue of 69.75±20.91 fmol/mg protein. Similarly, we have shown that the bovine pineal gland possesses a specific choline acetyltransferase with an activity of 0.034±0.004 nmol/mg protein/min. In order to delineate the function of these cholinergic receptor sites, we have studied the effects of muscarinic cholinergic receptor agonists on the activity of serotonin N-acetyltransferase, the melatonin synthesizing enzyme. Cholinergic receptor agonists such as methacholine (10 μM), carbachol (10 μM), and oxotremorine (10 μM) inhibited the activity of serotonin N-acetyltransferase in the bovine pineal explants in culture, from a control value of 5.02±0.45 to 1.25±0.25, 1.30±0.15, and 1.22±0.20 pmol/mg protein/min, respectively. These inhibitory effects were blocked by muscarinic cholinergic receptor antagonists such as atropine (20 μM) or QNB (20 μM). The presence of high affinity muscarinic cholinergic binding sites, of a specific choline acetyltransferase, along with an inhibitory action of cholinomimetic agents on the activity of serotonin N-acetyltransferase, are interpreted to suggest that muscarinic cholinergic fibers may modulate the synthesis and actions of pineal melatonin. © 1991 Plenum Publishing Corporation.